Advances in fertility preservation of female patients with hematological malignancies. Issue 11 (2nd November 2017) - Salama, Mahmoud; Isachenko, Vladimir; Isachenko, Evgenia; Rahimi, Gohar; Mallmann, Peter
ABSTRACT: Introduction : The most common forms of hematological malignancies that occur in female reproductive years are lymphoma and leukemia. Areas covered : Several aggressive gonadotoxic regimens such as alkylating chemotherapy and total body irradiation are used frequently in treatment of lymphoma and leukemia leading to subsequent iatrogenic premature ovarian failure and fertility loss. In such cases, female fertility preservation options should be offered in advance. Expert commentary : In order to preserve fertility of young women and girls with lymphoma and leukemia, several established, experimental, and debatable options can be offered before starting chemotherapy and radiotherapy. However, each of those female fertility preservation options has both advantages and disadvantages and may not be suitable for all patients. That is why a fertility preservation strategy should be individualized and tailored distinctively for each patient in order to be effective. Artificial human ovary is a novel experimental in vitro technology to produce mature oocytes that could be the safest option to preserve and restore fertility of young women and girls with hematological malignancies especially when other fertility preservation options are not feasible or contraindicated. Further research and studies are needed to improve the results of artificial human ovary and establish it in clinical practice.